O‘ZBEKISTONDA UCHRAYDIGAN MAHALLIY O‘SIMLIKLARNING YALLIG’LANISHGA QARSHI FAOLLIGINI O‘RGANISH (Journal of Science-Innovative Research in Uzbekistan, 2024)
There is any kind of disease, which certainly involves an inflammatory process. Nowadays, local plants are widely used in the treatment of many diseases. The development of folk medicine contributes to the reduction of inflammatory diseases. This article presents information about the molecular mechanisms of inflammatory disease and the anti-inflammatory activity of local plants used in folk medicine to combat it.